Baragan'in devedikenleri : by Panait Istrati. - Istrati, Panait., 1884-1935. (Istanbul : Oda, 1991)
Near East's complex social and humanly connections. Baragan humans's lives and feudal boyar's cruelty.
This book is in Turkish.
Keywords: Near East -- Baragan Humans -- Fiction